Effect of Waste Laundry Detergent Industry Against Mortality and Physiology Index of Nile Tilapia (Oreochromis niloticus) - Yuliani, Rifky Luvia; Purwanti, Elly; Pantiwati, Yuni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Laundry industry increasingly prevalent in Malang as many students who want instant leaching process. Waste generated in the form detergent wastes directly discharged into waters such as rivers and pollute the water environment and disrupt the lives of aquatic one of tilapia. Components of detergent can cause a decrease in dissolved oxygen (DO) in the water. The low DO disrupt the process of respiration and metabolism in fish. As a result, higher mortality and physiology index values as parameters impaired metabolism of the fish. Therefore, this studyÂ  purpose to: 1) determine the influence of industrial wastes laundry detergent on mortality and physiological indices of nile tilapia (Orechromis niloticus); and 2) the concentration of industrial wastewater laundry detergent that what has the highest mortality rate. This research method is RAL 3 repetitions and 6 treatments (0%, 1%, 2%, 3%, 4%, and 5%). The design of the study is only Posttest Control Design. The results showed the influence of industrial wastes laundry detergent on mortality and physiological indices of nile tilapia. The highest mortality of nile tilapia at a concentration of 5% as much as 6 tails. While the CF concentration of 0% at 1.92; 1% of 1.97; 2% of 1.95; 3% of 1.69; 4% by 1.51; and 5% of 1.23. LSI value of 0% concentration of 0.23; 1% of 0.33; 2% 0,58; 3% of 0.50; 4% 0,58; and 5% of 0.67. GSI value of 0% concentration of 0.93; 1% of 0.21; 2% of 0.28; 3% of 0.14; 4% of 0.21; and 5% by 0.26. Physiology index can be used as a biomarker of environmental biology to determine the level of pollution in waste waters.Keywords : laundry industry waste, mortality, physiological indices, nile tilapia.